Assessment of Genetic Variability for Yield and Yield Components in Rice (Oryza sativa L.) Germplasms - Pratap, Akhand; Bisen, Prashant; Loitongbam, Bapsila; Sandhya; Singh, P. K. (International Journal of Bio-resource and Stress Management, 2018)
Thirty eight rice germplasms were evaluated to assess their genetic variability, heritability, genetic advance, correlation and direct- indirect effect for grain yield and yield contributing traits. The analysis of variance revealed significant differences for all the characters under study, indicating the presence of high genetic variability among the genotypes. The genotype CRR599-4-1 was found to be the best for grain yield and effective tiller plant-1, panicle length, test weight and spikelet fertility per cent on the basis of per se performance. The high estimates of GCV and PCV were observed for traits like grain yield per plant, filled grains panicle-1, effective tillers plant-1 indicating their importance in selection for improving the rice yield. High heritability coupled with high expected genetic advance as percent of mean was observed for the traits field grain panicle-1, spikelet fertility percentage and days to maturity. Grain yield plant-1 had strong positive association with spikelet fertility percentage, filled grain panicle-1, effective tiller plant-1, plant height and test weight and significant positive correlation with plant height, effective tillers plant-1, test weight, filled grains panicle-1 and spikelet fertility. Path coefficient analysis revealed that days to 50% flowering, plant height, number of effective tiller, panicle length, test weight and filled grain panicle-1 exhibit positive direct effect on grain yield plant-1.